2022
DOI: 10.14336/ad.2022.1114
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation in Disorders of Consciousness: An Update and Perspectives

Abstract: Disorders of consciousness (DOC) is a state in which consciousness is affected by brain injuries, leading to dysfunction in vigilance, awareness, and behavior. DOC encompasses coma, vegetative state, and minimally conscious state based on neurobehavioral function. Currently, DOC is one of the most common neurological disorders with a rapidly increasing incidence worldwide. Therefore, DOC not only impacts the lives of individuals and their families but is also becoming a serious public health threat. Repetitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…As early as 2009, Louise-Bender Pape et al (2009) found that DOC patients tended to show significant neurobehavioral improvements that were temporally associated with the delivery of rTMS. Recently, Huang et al (2023) reported the efficacy and possible mechanisms of rTMS for DOC and discussed the potential key parameters that affected the therapeutic efficiency of rTMS in DOC patients. Additionally, iTBS was a novel rTMS model that may be suggested as a potential therapeutic intervention of DOC ( Wu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…As early as 2009, Louise-Bender Pape et al (2009) found that DOC patients tended to show significant neurobehavioral improvements that were temporally associated with the delivery of rTMS. Recently, Huang et al (2023) reported the efficacy and possible mechanisms of rTMS for DOC and discussed the potential key parameters that affected the therapeutic efficiency of rTMS in DOC patients. Additionally, iTBS was a novel rTMS model that may be suggested as a potential therapeutic intervention of DOC ( Wu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroscientists are investigating ways to accelerate the improvement of consciousness in DOC patients while promoting functional recovery. Neuromodulation therapy has shown beneficial effects in promoting recovery after traumatic brain injury, but existing treatments such as transcranial magnetic stimulation, deep brain stimulation (DBS) and hyperbaric oxygen therapy still need further systematic studies to demonstrate their mechanisms of action ( Rezaei Haddad et al, 2019 ; Chen et al, 2022 ; Huang et al, 2023 ). The brain function is mediated by the interaction between different neural circuits and neurons in brain regions.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Repeated transcranial magnetic stimulation has been explored in treatment of vs and MCS, but its clinical efficacy is still controversial and awaits confirmation through high-quality intervention studies. 15 16 In addition, it is still unclear whether benefits of invasive brain stimulation outweigh its risks in the treatment of DoC. 17–19 Therefore, novel and more effective therapeutic interventions for pDoC are needed.…”
Section: Introductionmentioning
confidence: 99%